BLOOD BIOCHEMICAL LIVER PROFILE OF VICUNAS (VICUGNA VICUGNA) RAISED IN CAPTIVITY IN LIMA - Concha P., Arleni (2013)
The blood biochemical liver profile in vicunas (Vicugna vicugna) was determined using 31 animals reared in captivity in two zoological parks in the city of Lima, Peru. Blood was collected by puncture of the jugular vein to measure total (BT), direct (BD) and indirect bilirubin (BI), alanine amino transferase (ALT), aspartate amino transferase (AST), alkaline phosphatase (FA), gamma glutamyl transferase (GGT), total protein (PT), albumin, globulin and glucose. The values (mean ± sd) were: BT 0.27 ± 0.10 mg/dl; BD 0.10 ± 0.06 mg/dl; BI 0.17 ± 0.09 mg/dl; ALT 6.39 ± 4.62 UI/L; AST 242.77 ± 61.36 UI/L; FA 175.16 ± 67.23 UI/L; GGT 11.32 ± 9.84 UI/L; PT 8.27 ± 2.25 g/dl; albumin 4.06 ± 0.82 g/dl; globulins 4.21 ± 1.93 g/dl; glucose 143.16 ± 33.14 mg/dl. No statistically difference due to sex was found but rearing location was significantly different (p<0.05) for PT, albumin and globulins.